Recurrent ameloblastoma 24 years after hemimandibulectomy: A case report and review of literature - Saravanan Balasubramaniam; Balaji Jayaraman; Rohini Thirunavukkarasu; Arun Kumar Kamalakaran (Wolters Kluwer Medknow Publications, 2019)
Ameloblastoma is a benign, locally aggressive epithelial odontogenic tumor with a high recurrence rate. The management of ameloblastoma has always been controversial and an enigma to the surgeons. Literature suggests that 50% of the recurrences occur during first 5 years after the primary surgery, and the recurrence rate following a radical approach such as a segmental resection is 4.6%. The reasons for recurrence after a radical approach can be multifactorial such as remaining stumps, soft tissues, or intraoperative contamination. The purpose of this case report is to emphasize the fact that a recurrence even after 24 years is possible in spite of a radical segmental resection, and hence, a continuous follow-up of the patient is needed and to highlight the fact that the possibility of malignant ameloblastoma or ameloblastic carcinoma should be ruled out when dealing with such ameloblastomas recurring after a long period after a radical primary surgery.